Determining the factors affecting medical tourism destination choice: empirical evidence from Malaysia / Hafizah Arifin, Puteri Aliza Megat Ramli and Norlida Che Hassan - Arifin, Hafizah; Megat Ramli, Puteri Aliza; Che Hassan, Norlida (2022)
Medical tourism is a relatively new market segment that has gained the attention of major health care leaders in a variety of countries over the previous decade. Based on prior literature, there are limited study has been conducted on medical tourism destination selection. This study shall examine Malaysia as a medical tourism destination choice and determining whether the factors of lower cost, facilities, service quality, accessibility, tourist attraction may influence medical tourists to select Malaysia as a destination choice. Purposive sampling technique was applied for the study. Questionnaires were distributed using online platform to the foreigners who stay outside Malaysia particularly to those who know and understand the English. 115 completed questionnaires were collected through Medical Tourism Agency Website and their overseas branch and data has been analyzed using IBM SPSS 20 version. The statistical analysis used in the study are descriptive analysis, reliability analysis, mean score analysis of variables, frequency analysis, multicollinearity and regression analysis. The findings revealed that lower costs, accessibility of information and tourist attraction have significant impact on medical tourism destination selection. This research can be beneficial for the healthcare provider, insurance company and tourism industry to improve and enhance their policies, benefits programs and initiatives inside the organization and industry. Furthermore, the findings can be used to enhance the strategies by the policy maker especially in the context of marketing and strategic partnership.